Six potential biomarkers in septic shock: a deep bioinformatics and prospective observational study - Kong, Chang; Zhu, Yurun; Xie, Xiaofan; Wu, Jiayu; Qian, Meizi (Frontiers in Immunology, 2023)
Background Septic shock happens when sepsis is related to severe hypotension and renders remarkable deaths. Early diagnosis of septic shock was essential to reducing mortality. We identified a risk-score model based on gene signature to elevate predictive efficiency. Methods DEGs were identified from gene expression profiles merged from GSE33118 and GSE26440 through limma package in R software. Kyoto Encyclopedia of Genes and Genomes pathway enrichments and Gene Ontology were performed. Hub genes were identified via Boruta and lasso regression. In GSE9692, septic shock-related gene modules were identified using Weighted Gene Co-expression Network Analysis and compared with DEGs. Gene set enrichment analysis and CIBERSORT were performed to study hub gene function and signaling pathways and the immune cell infiltration pattern. The diagnostic value of hub genes in septic shock was measured using ROC analysis, and verified through hospital patient PCR and Western blotting. Results A total of 975 DEGs in GSE33118 database and GSE26440 database were obtained, of which remarkably upregulated DEGs were 30. Through Lasso regression and Boruta feature selection algorithm, six hub genes (CD177, CLEC5A, CYSTM1, MCEMP1, MMP8 and RGL4) with expression differences in septic shock were screened as potential diagnostic markers for septic shock. Weighted gene co-expression network analysis (WGCNA) was used to identify the co-expression modules and module–trait correlation. Enrichment analysis showed significant enrichment in the reactive oxygen species pathway, hypoxia, PI3K/AKT/mTOR signaling, NFκ-β/TNFα and IL6/JAK/ STAT3 signaling pathways. The receiver operating characteristic curve (ROC) of these signature genes was 0.938, 0.914, 0.939, 0.956, 0.932 and 0.914, respectively. In the immune cell infiltration analysis, the infiltration of M0 macrophages, activated mast cells, neutrophils, CD8 T cells, and naive B cells were more significant in the septic shock group. In addition, higher expression levels of CD177, CLEC5A, CYSTM1, MCEMP1, MMP8 and RGL4 mRNA as well as higher expression levels of CD177 and MMP8 protein were observed in PBMCs isolated from septic shock patients than healthy donors. Conclusions CD177, CLEC5A, CYSTM1, MCEMP1, MMP8 and RGL4 were identified as hub genes, which were of considerable value in the early diagnosis of septic shock patients.